The impact of formal adult education on the likelihood of being employed: A comparative overview - Elina Kilpi-Jakonen; Daniela Vono de Vilhena; Yuliya Kosyakova; Anders Stenberg; Hans-Peter Blossfeld (allinn University Institute of Political Science and Governance and Tallinn University Institute of International and Social Studies, 2022)
This article aims to map formal adult education in terms of the determinants of educational upgrading later in life, relating these back to social inequalities from a comparative perspective, and to labour market outcomes following participation, particularly the probability of being employed. It relies on a longitudinal analysis of data from the United Kingdom, Spain, Sweden and Russia. Results show that educational upgrading at mature ages has the potential for reducing social inequalities in all the countries analysed. Upgraders tend to come from a medium to low education background in Russia and the UK but from the tertiary educated in Spain and Sweden. Labour market marginalisation increases the chance of upgrading particularly in Sweden. Upgrading tends to increase employment opportunities, though these are in some cases conditional on being employed whilst studying. This is specifi cally the case for Russia and for men in the UK. We also found important country-specifi c gender diff erences in the eff ect of upgrading on employment opportunities, according to which women benefi t more than men in the UK and Sweden. We conclude with some suggestions about the institutional eff ects that produce diff erences between countries.